Determinant Analysis Related to the Implementation of Occupational Safety and Health Culture in Workers of the Bulango Ulu Dam Project Pt. Hutama-Basuki-Lestari, KSO - Osama; Herlina Jusuf; Putri Ayuningtias Mahdang (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
K3 culture is the attitudes, values, beliefs, norms, and perceptions that underlie safe behavior in the work process and its practical application to create a safe and healthy work environment for all workers. The formulation of what determinant problems are related to the implementation of occupational safety and health culture in the workers of the Bulango Ulu Dam project of PT. Hutama-Basuki-Lestari, KSO. This study aims to analyze determinants related to the implementation of occupational safety and health culture in workers of the Bulango Ulu Dam project of PT. Hutama-Basuki-Lestari, KSO. The design of the quantitative research uses an analytical survey with a Cross Sectional design. The research population was 43 workers. The sampling technique in this study uses the total sampling technique. Data analysis using Chi-Square test and Rank-Spearman test. The results of this study show that there is a significant relationship between K3 knowledge, K3 training, safety patrol, and safety talk to the implementation of occupational safety and health culture in workers of the Bulango Ulu Dam project of PT. Hutama-Basuki-Lestari, KSO with a value of p = 0.000 (p ? 0.05). It is recommended that companies improve K3 training, especially for workers with low education, increase safety patrol personnel, and make safety talks more interactive. Strict enforcement of sanctions is also needed to strengthen the K3 culture.